Effect of number of stages on the performance characteristics of modified Savonius hydrokinetic turbine. (1st December 2020) - Kumar, Anuj; Saini, R.P.; Saini, Gaurav; Dwivedi, Gaurav
Abstract: Savonius hydrokinetic turbine is considered as an environmentally friendly and cost effective turbine to extract hydrokinetic potential available in flowing streams. However, this turbine has not been fully explored, as the solution for the main problem of low efficiency of Savonius turbine is still being investigated around the globe. In order to study the effect of number of stages, this study aims to analyze the performance of modified Savonius hydrokinetic turbine having twisted blade under different values of number of stages. A commercial unsteady Reynolds-Averaged Navier-Stokes (URANS) solver in conjunction with realizable k-ε turbulence model has been used for the numerical analysis. Pressure and velocity distribution found around the rotor have also been analyzed and discussed. Based on the present investigation, the maximum power coefficient value of 0.44 is obtained for double stage turbine corresponding to tip speed ratio (TSR) value of 0.9 at Reynolds number of 37.53 × 10 4 . Using numerical data obtained, correlation has been developed for power coefficient as a function of number of stages Reynolds number and tip speed ratio. Highlights: Effect of multi-stages on performance of Savonius hydrokinetic rotor is studied. CFD investigation is carried out for Reynolds number ranging from 9.38 × 10 4 to 37.52 × 10 4 . Flow distribution around the Savonius hydrokinetic turbine is discussed. A correlation for power coefficient is also developed.